BIMBINGAN TEKNIS BAGI CALON PENGUJI MAHASISWA PENDIDIKAN PROFESI GURU (PPG) DI UNIVERSITAS MUHAMMADIYAH KOTABUMI - Rulik Setiani; Fhela Vhantoria Ningrum (Penerbit Widina, Widina Media Utama, 2026)
Technical guidance for prospective Teacher Professional Education Performance Test (UKPPPG) examiners is essential to improve the quality of assessment by ensuring objectivity, transparency, and compliance with national standards. This study aimed to analyze the effectiveness of technical guidance in enhancing the competence of prospective UKPPPG examiners at Universitas Muhammadiyah Kotabumi. The program was conducted over two days through online and offline sessions as part of a Community Service Program, involving 20 prospective examiners consisting of 9 lecturers and 11 school teachers. The implementation included a pre-test, presentations on UKPPPG policies, training on assessment instruments and scoring rubrics, practice and simulation sessions, discussions, and a post-test. The results demonstrated improved participant competence, as reflected by the increase in the proportion of participants achieving scores of ?70, from 35% in the pre-test to 80% in the post-test. Participants also showed better understanding of assessment instruments and greater readiness to conduct objective assessments. Therefore, the technical guidance effectively enhanced the competence, professionalism, and integrity of prospective UKPPPG examiners. ABSTRAKBimbingan teknis (bimtek) bagi calon penguji Uji Kinerja Pendidikan Profesi Guru (UKPPPG) diperlukan untuk meningkatkan kualitas asesmen yang objektif, transparan, dan sesuai standar nasional. Kegiatan ini bertujuan menganalisis efektivitas bimtek dalam meningkatkan kompetensi calon penguji UKPPPG di Universitas Muhammadiyah Kotabumi. Bimtek dilaksanakan selama dua hari secara daring dan luring sebagai bagian dari program Pengabdian kepada Masyarakat (PkM), melibatkan 20 calon penguji yang terdiri atas 9 dosen dan 11 guru. Metode pelaksanaan meliputi pre-test, penyampaian materi kebijakan UKPPPG, pembekalan instrumen dan rubrik penilaian, latihan dan simulasi, diskusi, serta post-test. Hasil menunjukkan peningkatan kompetensi peserta, ditandai dengan kenaikan persentase peserta yang memperoleh nilai ?70 dari 35% pada pre-test menjadi 80% pada post-test. Selain itu, peserta menunjukkan pemahaman yang lebih baik terhadap instrumen dan rubrik penilaian serta kesiapan melaksanakan asesmen secara objektif. Dengan demikian, bimtek efektif meningkatkan kompetensi, profesionalisme, dan integritas calon penguji dalam mendukung mutu pelaksanaan UKPPPG.